Wideband Continuous-time ΣΔ ADCs, Automotive Electronics, and Power Management Advances in Analog Circuit Design 2016 - Baschirotto, Andrea; Harpe, Pieter; Makinwa, Kofi A. A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is based on the 18 tutorials presented during the 25th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, including low-power and energy-efficient analog electronics, with specific contributions focusing on the design of continuous-time sigma-delta modulators, automotive electronics, and power management. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development.
Part I CT MASH Architectures for Wideband ΔΣ Modulators -- 1 WiFi Receiver Evolution in a Dense Blocker Environment -- 2 WiFi Receiver Evolution in a Dense Blocker Environment -- 3 ΣΔ ADCs with Improved Interferer Robustness -- 4 Design Considerations for Filtering ΔΣ Converters -- 5 Blocker and Clock-Jitter Performance in CT ΔΣ ADCs for Consumer Radio Receivers -- 6 CT MASH Architectures for Wideband ΔΣ Modulators -- Part II - Automotive Electronics -- 7 Trends and Characteristics of Automotive Electronics -- 8 Next Generation of Semiconductors for Advanced Power Distribution in Automotive Applications -- 9 High-Voltage Fast-Switching Gate Drivers -- 10 A Self-Calibrating SAR ADC for Automotive Microcontrollers -- 11 Advanced Sensor Solutions for Automotive Applications -- 12 A Low Power Continuous Time Accelerometer Front End -- 13 Part III Power Management -- 14 Switched-Capacitor Power Converter Topology Overview and Performance Comparison -- 15 Switched-Capacitor Power Converter Topology Overview and Performance Comparison -- 16 Heterogeneous Integration of High-Switching Frequency Inductive DC/DC Converters -- 17 Heterogeneous Integration of High-Switching Frequency Inductive DC/DC Converters -- 18 Heterogeneous Integration of High-Switching Frequency Inductive DC/DC Converters -- 19 An Ultra-Low-Power Electrostatic Energy Harvester Interface.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation